Analysis of Organizational Culture and Work Environment to the Satisfaction of Outpatients Room in Public Health Center of Bangsal Mojokerto Regency - Ulfah Kurniasari; Koesnadi Koesnadi; Endra Widiyanto (Journal for Quality in Public Health, 2021)
The satisfaction of health care users is closely related to the results of health services, both medically and non-medically such as compliance with treatment. Problems regarding performance in Puskesmas Bangsal greatly impact the services provided to patients that can be seen from the decrease in the number of patient visits to upt Puskesmas Bangsal Mojokerto Regency. The purpose of this study was to find out the influence of organizational culture and work environment (temperature, air, noise, lighting) on the satisfaction of outpatients in Mojokerto District Ward Health Center The design of this research is analytics with a crossectional approach. The variables of this study are organizational culture and work environment (temperature, air, noise and lighting) as independent variables and satisfaction as dependent variables. The research population is all outpatients who visited the Outpatient Health Center Mojokerto in January - June 2020 as many as 1,984 outpatients. Samples were taken with random sampling techniques as many as 397 respondents. The data was collected with questionnaire instruments and processed using editing, coding, scoring and tabulating and tested with linear regression tests. The results of this study showed that partially or alone – independent variables can affect the occurrence of dependent variables due to the value of < of 0.05. Independent variables affecting simultaneously or together can affect patient satisfaction and the relationship between the two variables shows a close relationship with a coefficient value of 99.1%. The results of this study show the organizational culture and work environment is one aspect of the management of health center services that can affect patient satisfaction in receiving services, so it is expected that management can improve these aspects optimally so that patient satisfaction can be further improved